2003
DOI: 10.1128/aem.69.12.7137-7144.2003
|View full text |Cite
|
Sign up to set email alerts
|

Real-TimePCR Analysis of Vibrio vulnificus fromOysters

Abstract: Vibrio vulnificus is an opportunistic human pathogen commonly found in estuarine environments. Infections are associated with raw oyster consumption and can produce rapidly fatal septicemia in susceptible individuals. Standard enumeration of this organism in shellfish or seawater is laborious and inaccurate; therefore, more efficient assays are needed. An oligonucleotide probe derived from the cytolysin gene, vvhA, was previously used for colony hybridizations to enumerate V. vulnificus. However, this method r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 41 publications
2
94
0
1
Order By: Relevance
“…However, after 14 days, the determination coefficient (R 2 ) was low at 0.747, indicating that the efficiency of extraction had declined. This result supported that such starved cells in the environment are unlikely to be lysed 3) , causing underestimation of the real-time quantification.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…However, after 14 days, the determination coefficient (R 2 ) was low at 0.747, indicating that the efficiency of extraction had declined. This result supported that such starved cells in the environment are unlikely to be lysed 3) , causing underestimation of the real-time quantification.…”
supporting
confidence: 70%
“…The detection limits (10 2 cells/ml) of direct counts were not changed during the 14 day experiment, showing determination coefficients (R 2 ) of 0.971, 0,976, and 0.747, at 0 day, 7 days, and 14 days, respectively. It was reported that nonculturable cells of V. vulnificus after incubation in ASW at 4°C were detected by real-time PCR, unless complete degradation of membranes or loss of nucleic acid occurred 3) . However, after 14 days, the determination coefficient (R 2 ) was low at 0.747, indicating that the efficiency of extraction had declined.…”
mentioning
confidence: 99%
“…V. vulnificus biotype 1 strains added to the collection included nine environmental strains from the Tampa Bay region of the Gulf of Mexico and one clinical strain from the Florida Department of Public Health, kindly provided by Valerie Harwood; previously described clinical strains MO6-24/0 (25,51,60) and ATCC 23907 (25); MLT365, MLT367, MLT403, VV1009, 2400112, and LL728, previously examined by our group for virulence (51,52); and genomically sequenced strains CMCP6 (29) and YJ016 (13). All strains were confirmed as V. vulnificus by species-specific vvhA PCR and DNA probe as previously described (10,59).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures that did not amplify by PCR at this locus were also analyzed for the presence of individual genes using primers derived from either wza (wzaF1 and wzaR [5Ј-TCGCGT TATCTGATCAACCA-3Ј]), wzb (wzbF [5Ј-GGTTGATCAGATAACGCGAA-3Ј] and wzbR [5Ј-AAGGAATACAAGCGTCTAGG-3Ј]), wzc (wzcF2 [5Ј-CCC GGAAATGAACGAGACAATG-3Ј] and wzcR2), or wbfV (wbfVF [5Ј-CTA TCGTAGATGTGGATATTGAG-3Ј] and wbfVR). Additionally, vvhA primers were used to test the stability of chromosomal DNA, using PCR conditions as previously described (6).…”
Section: Methodsmentioning
confidence: 99%